The Name of the University: The Symbolic Naming Policy of the Elisabeth University - Polyák, Petra (Per Aspera ad Astra, 2024)
The name of a university is a symbol intended for the general public, and the choice of an eponym is the most visible act of the institution's symbolic and remembrance policy. This is why it often becomes a source of conflict. The name of the Royal Hungarian Elizabeth University of Bratislava has changed five times since its foundation in 1912. As certain elements of the name carried different and crucial identity connotations related to the self-definition of the institution, any internal or external initiative to change/delete them provoked strong (and usually negative) reactions at the university. This was the case, for example, with the rejection of the name of the new seat, Pécs, which expressed the symbolic attachment to Bratislava, the place of its foundation, or the attempts to fit the dynastic eponym into the discourse of the post-1945 “democratic”, but already partly Sovietized political establishment. The mostly inevitable changes of the name elements of the Elizabeth University also mark the most important political turning points of the first half of the 20th century, but they were not simply a reflection of political changes in the public law. Since each element of the name represented a specific part of the identity of the university, their change also led to a transformation of institutional self-definition.